Authoritarian Parenting Style and Its Relationship with Child Development: A Study of Families in Semarang, Indonesia - Prihantanti, Leonita Bella; Nurmasitah, Sita (Universitas Negeri Semarang, 2025)
This study examines the relationship between authoritarian parenting and child development among families in Semarang, Indonesia. Using a cross-sectional quantitative approach, 60 parents of children aged 3–7 years were surveyed through a Likert-scale questionnaire grounded in Baumrind’s parenting style theory and Erikson’s psychosocial development stages. Data were analyzed using Pearson correlation. Findings revealed a very weak negative correlation (r = -0.007, p > 0.05), suggesting no statistically significant relationship between authoritarian parenting and child development in the studied context. These results highlight that child development is more strongly influenced by external factors such as extended family support, socioeconomic conditions, and cultural values. This study contributes to the global debate on parenting by emphasizing the contextual and cultural variability of authoritarian parenting effects. Practical implications suggest that interventions to enhance child development should adopt a holistic and ecosystem-based approach, involving parents, schools, and communities rather than focusing solely on parenting style.